Ecosystem Services A Challenge and Opportunity in Mining Industry Investment - Arief Nur Muchamad (Universitas Muhammadiyah Mataram, 2023)
Understanding ecosystem services was initially developed to define the advantage natural ecosystems produce for society and raise awareness for biodiversity and ecosystem conservation. Ecosystems are capital assets, feasible of attention and investment given to other forms of capital. Recently, the trend of investment through a capital loan for the development of the mining and metal industry has increased. Several financing agencies have incorporated ecosystem services into industrial operations' risk and impact assessment systems to fulfil their standards. This study aims to identify significant challenges and opportunities for ecologists or environmentalists involved in research or modelling ecosystem services, especially in the mining industry. To reveal the relationship between ecosystem services challenge and opportunity in investment, a paper review related to ecosystem services was conducted. The challenge is to discover meaningful and robust indicators to quantify ecosystem services. Biodiversity manages the capacity of the environment to present ecosystem services, can be directly gathered to meet the material requirements of individuals and is valued by social orders for its intangible commitment to prosperity.